2016
DOI: 10.1124/dmd.116.072462
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Differential Regulation of Cytochrome P450 Enzymes in Type 1 Allergic Mice

Abstract: Type 1 allergic diseases are characterized by elevated production of specific immunoglobulin E (IgE) for each antigen and have become a significant health problem worldwide. This study investigated the effect of IgE-mediated allergy on drug pharmacokinetics. To further understand differential suppression of hepatic cytochrome P450 (P450) activity, we examined the inhibitory effect of nitric oxide (NO), a marker of allergic conditions. Seven days after primary sensitization (PS7) or secondary sensitization (SS7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 45 publications
0
8
2
Order By: Relevance
“…Concerning the contribution of T helper 2 cell-activated immune systems, little information is available on the ability of cytokines to directly regulate FMO1 and FMO3 expression. We reported that CYP1A2, CYP2C, CYP2E1, and CYP3A activities were markedly suppressed by allergy-induced NO production-but not the cytokine-dependent pathway-resulting in marked changes in drug pharmacokinetics (Tanino et al, 2016). Our results differed from the significant contribution of T helper 1 cellactivated proinflammatory cytokines (cytokine-dependent pathway) in lipopolysaccharide-stimulating inflammatory diseases (Renton 2001(Renton , 2004Morgan et al, 2008).…”
Section: Introductioncontrasting
confidence: 69%
See 4 more Smart Citations
“…Concerning the contribution of T helper 2 cell-activated immune systems, little information is available on the ability of cytokines to directly regulate FMO1 and FMO3 expression. We reported that CYP1A2, CYP2C, CYP2E1, and CYP3A activities were markedly suppressed by allergy-induced NO production-but not the cytokine-dependent pathway-resulting in marked changes in drug pharmacokinetics (Tanino et al, 2016). Our results differed from the significant contribution of T helper 1 cellactivated proinflammatory cytokines (cytokine-dependent pathway) in lipopolysaccharide-stimulating inflammatory diseases (Renton 2001(Renton , 2004Morgan et al, 2008).…”
Section: Introductioncontrasting
confidence: 69%
“…Patients with bronchial asthma and allergic rhinitis show an increased level of nitric oxide (NO) in exhaled air (Alving et al, 1993;Kharitonov et al, 1997). We also found that type 1 allergy with high serum IgE concentrations enhance serum NO concentrations (Tanino et al, 2016). Park et al (1999) suggested that excessive activation of the https://doi.org/10.1124/dmd.117.076570.…”
Section: Introductionmentioning
confidence: 71%
See 3 more Smart Citations